Sistem Navigasi Keselamatan Pelayaran Perairan Darat Berbasis Web - Anton Widodo; I Putu Putra Wira Sarwa Yudha; Maulana Putra; Agustina Rachmawardani; Nardi Nardi (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Navigation safety in inland waters is often threatened by extreme weather conditions such as strong winds and high waves. This study developed SIGADANA, a web-based navigation system that provides early warnings of weather and water conditions in seven major ports: Ajibata, Ambarita, Balige, Muara, Simanindo, Sipinngan, and Tigaras. The system integrates real-time data with hourly temporal intervals from the OpenMeteo API, including wind speed, wind direction, temperature, and humidity, and utilises the JONSWAP model with Boussinesq corrections to estimate significant wave height (Hs) based on local topography and water depth. Furthermore, to assist the analyst team in understanding weather and water patterns in the test area, the system also stores early warning data for a five-year period, 2020-2024. SIGADANA has three main features: (1) historical monitoring of water condition trends, (2) real-time predictions for early warnings up to two hours in advance, and (3) navigation route advisories. To date, particularly in Indonesia, there has been no project estimating wave conditions prior to SIGADANA. Therefore, the system was only evaluated using OLS regression, with results showing that the model was able to explain more than 70% of the data variation. However, there are indications of residual autocorrelation and potential multicollinearity that need to be considered in the interpretation. In the future, SIGADANA is expected to improve navigation safety and has the potential to become a model for other inland waters in Indonesia.